P12 Exploring the characteristics of patients with mesothelioma who decline chemotherapy: a prospective cohort of 200 patients. (15th November 2016) - Bibby, AC; Fonseka, D De; Morley, AJ; Keenan, E; Addeo, A; Smith, S; Edey, AJ; Maskell, NA
Abstract : Introduction: Malignant pleural mesothelioma (MPM) is an aggressive cancer with a poor prognosis. Treatment options are limited, and pemetrexed and cisplatin chemotherapy is the only intervention shown to extend life. Promising new therapies may provide alternate treatment options in the future. Chemotherapy uptake varies in MPM. Some centres report rates as low as 46% in eligible patients. The aim of this study was to explore the characteristics of patients who declined chemotherapy, and to determine which factors were associated with chemotherapy refusal. Methods: Prospective data were collected on all patients diagnosed with MPM in one UK tertiary referral centre. Diagnosis of MPM and eligibility for chemotherapy were determined at the regional MPM multidisciplinary meeting. Patients were followed up until death or censored on 13/7/16. Patient characteristics were compared using chi-squared, Fishers Exact and unpaired T-tests. Kaplan Meier curves were drawn to compare survival between patients who accepted and declined chemotherapy. Logistic regression was used to assess associations between patient characteristics and chemotherapy uptake. Results: 200 patients were diagnosed with MPM between 1/3/08 and 8/6/16. 150 (75%) were eligible for chemotherapy. 93/150 (62%) patients received chemotherapy, 46/150 (31%) declined and 11/150 (7.3%) patients did not receive it for other reasons. Patient characteristics are shown in Table 1 . The group who declined chemotherapy were older (mean age 74.4 vs 68.4, p < 0.001), with a higher proportion of females (23.9% vs 10.8%, p = 0.041) and fewer patients with performance status (PS) 0 (17.4% vs 43%, p = 0.005). Patients who received chemotherapy had longer median survival (426 days vs 203 days, p = 0.001, HR 0.519, p = 0.015). The factors associated with chemotherapy refusal were age (regression coefficient 0.144, p < 0.001) and PS ≥ 1 (coefficient 1.052, p = 0.027). Conclusion: This is the first study to report the characteristics of MPM patients who declined chemotherapy. Significant differences were seen compared with patients who received chemotherapy. Further research is needed to determine whether similar patterns are seen in other centres. Reasons for refusal were not collected, but the association with age and worse performance status may reflect concerns about chemotherapy toxicity. Qualitative research could explore patients' reasons for refusing chemotherapy.